E0496 Comparative study of impaired with normal left ventricle function patients with triple coronary artery disease. (17th November 2010) - Zhan, Gao; Yue-Jin, Yang; Bo, Xu; Ji-Lin, Chen; Shu-Bin, Qiao; Yong-Jian, Wu; Xue-wen, Qin; Min, Yao; Hai-bo, Liu; Jin-Qing, Yuan; Jue, Chen; Shi-Jie, You; et al.
Abstract : Background: Ischaemic cardiomyopathy is one of the fatal courses of coronary heart disease, its clinical characteristics and percutaneous coronary intervention (PCI) effect on it still need to be identified. Methods: From April 2004 to April 2007, 4494 consecutive patients with triple coronary arteries disease identified by coronary angiogram (>70% stenosis of each vessel) in our center were divided into two groups according to left ventricle ejection fraction (LVEF) (N group: n=4129, LVEF>40%; L group: n=365, LVEF≤40%). Results: Patients in L group was younger (60.6±9.72 vs 65.2±10.7 years; p<0.001). There was more previous myocardial infarction (MI) and diabetes and less hypertension and hyperlipidaemia in L group. Logistic regression analysis indicated that the age, previous MI, diabetes, previous PCI and hyperlipidaemia were independent indexes to left ventricle function of triple vessel disease. Eighty-three and 2301 patients in L and N group (22.7% and 55.7%, respectively) were treated with PCI. The follow-up period of L and N groups were 581±298 and 639±293 days, respectively. MACE rate was significantly high in L group (38.6% vs 18.9%; p<0.001), which was contributed by cardiac death, no fatal MI and TVR (9.6% vs 0.9%; p<0.001, 7.2% vs 2.0%; p<0.001 and 21.7% vs 16.0%; p=0.173, respectively). There was no difference of total stent thrombosis or its components in both groups (total: 3.9% vs 3.5%; p=1.000, early: 0.2% vs 0.9%; p=0.256, late: 0.7% vs 1.3%; p=0.404 and very late: 3.1% vs 1.3%; p=0.201, respectively). Seven month Angiographic follow-up indicated that both in-stent and in-segment restenosis rate were significantly higher in L group (21.0% vs 11.1%; p=0.034 and 24.0% vs 12.2%; p=0.018). Conclusion: This one center, large sample study showed clinical characteristics of ischaemic cardiomyopathy, MI and diabetes might contribute to its morbidity, and PCI might prevent its morbidity. PCI of patients with triple coronary arteries disease and impaired left ventricle (LV) function leaded to worse outcomes when compared with normal LV function.